The viability of compost and biochar bacteria through total count within different size group / Nur Aishah Mohd Yusof - Mohd Yusof, Nur Aishah (Faculty of Plantation and Agrotechnology, 2018)
Biochar and compost as a soil amendment has potential increased the soil pH and improve plant growth. Biochar has many agricultural benefits. It increases crop yield. It helps to enhance the number of bacteria that will help in degradation process that will help in soil fertility. It helps to prevent fertilizer runoff increased water holding capacity, fewer use fertilizers and diminishing agricultural pollution to the surrounding environment. These studies were conducted to study the presence of bacteria in compost and biochar derived from Empty Fruit Bunch (EFB). The presences of bacteria in EFB compost and biochar were studied by using serial dilution method. This study was carried out to calculate the number of colonies of bacteria based on group size which was large, medium and small. The colonies of bacteria were counted by using the colony forming unit or CFU method. The result showed the presence of bacteria in compost that is more as compared to EFB biochar with the highest number was 106. The result shows the number of bacteria colonies for incubation of EFB compost and biochar are more compared with biochar. It is has potential as a soil amendment for growth performance.